Heparin affects the interaction of kininogen on endothelial cells - Andrezza Justino Gozzo; Guacyara Motta; Ilana Cruz-Silva; Viviane Abreu Nunes; Nilana M.T. Barros; Adriana K. Carmona; Misako U. Sampaio; Yára M. Michelacci; Kazuaki Shimamoto; Helena B. Nader; Mariana S. Araújo (2011)
In the plasma kallikrein-kinin system, it has been shown that when plasma prekallikrein (PK) and high molecular weight kininogen (HK) assemble on endothelial cells, plasma kallikrein (huPK) becomes available to cleave HK, releasing bradykinin, a potent mediator of the inflammatory response. Because the formation of soluble glycosaminoglycans occurs concomitantly during the inflammatory processes, the effect of these polysaccharides on the interaction of HK on the cell surface or extracellular matrix (ECM) of two endothelial cell lines (ECV304 and RAEC) was investigated. In the presence of Zn+2, HK binding to the surface or ECM of RAEC was abolished by heparin; reduced by heparan sulfate, keratan sulfate, chondroitin 4-sulfate or dermatan sulfate; and not affected by chondroitin 6-sulfate. By contrast, only heparin reduced HK binding to the ECV304 cell surface or ECM. Using heparin-correlated molecules such as low molecular weight dextran sulfate, low molecular weight heparin and N-desulfated heparin, we suggest that these effects were mainly dependent on the charge density and on the N-sulfated glucosamine present in heparin. Surprisingly, PK binding to cell- or ECM-bound-HK and PK activation was not modified by heparin. However, the hydrolysis of HK by huPK, releasing BK in the fluid phase, was augmented by this glycosaminoglycan in the presence of Zn2+. Thus, a functional dichotomy exists in which soluble glycosaminoglycans may possibly either increase or decrease the formation of BK. In conclusion, glycosaminoglycans that accumulated in inflammatory fluids or used as a therapeutic drug (e.g., heparin) could act as pro- or anti-inflammatory mediators depending on different factors within the cell environment.